(untitled) (DAPesquisa, 2021)
This article presents the results of a master’s dissertation that approaches an investigative path on the concepts of oppositional dress and oppositional embroidery, through approaches between the fields of fashion design and politics. In addition to a historical take, significant changes in ways of life are listed, which occurred in the second half of the 20th century in conjunction with clothing and embroidery. In this context, the concept of resistance is outlined in the production of contemporary subjectivity, from the approach of costumes and embroidery presented in two case studies. The first is a collection of clothing by the fashion designer from Minas Gerais, Zuzu Angel, created in 1971 during the Brazilian civil-military dictatorship (1964-1985). The second, inserted in the political scenario of the last decade (2010-2020), analyzes the embroidered pamphlets of the São Paulo collective Linhas de Sampa, carried out in the last two years. The research focuses on the powers of the oppositional dress and embroidery as dissonant narrative factors, which create expressive spaces that question social hegemony for expanding the articulations between the fields of design and politics.